Vocational training of specialists for the hospitality and restaurant industry in the conditions of distance learning - Bezruchenkov, Yu. (Problems of Engineer-Pedagogical Education, 2021)
The challenge of training specialists for the hospitality and restaurant industry by means of distance technologies consists in the mismatch of the modern education system with the requirements of the digital economy, which is in a growing need of competent specialists who can use mobile devices, navigate in a rapid information flow in order to structure, analyse and select the necessary information. Studying with the use of distance learning technologies within the framework of distance education in the context of a personality-oriented approach appears to be a possible solution to this problem. The aim of the study is to identify the most effective approach to training of hotel and restaurant specialists in the context of the need to use distance learning technologies. A personality-oriented approach is considered to be the dominant paradigm of modern education, in the process of which the interaction of subjects of education is aimed at the professional development of future specialists. New approaches to teaching require the presence of new generation teachers who are, on the one hand, familiar with the methods of the personality-oriented approach and, on the other hand, capable and ready to use distance technologies and develop interactive teaching materials. In this regard, special training / retraining / advanced training of university teachers seem expedient. The study widely applies the methods of the personality-oriented approach and the anthropological approach. The problems that are solved by students and teachers in distance learning during the process of training hotel and restaurant specialists are highlighted. It is shown that the effectiveness of distance learning is conditioned by the use of pedagogical technologies that distance learning courses are based on and provides a real opportunity to get an education or improve your knowledge in certain subjects using the most innovative and prominent pedagogical methods.